Convergence and Divergence in the EU: Lessons from Italy - Barry Eichengreen (Intereconomics, 2019)
The topic of the Intereconomics/CEPS conference for which this paper was written was framed as a question: convergence or divergence in the EU? I am prepared to give an unambiguous answer. That answer is yes.
Keywords: 330; Economic convergence; EMU; EU; Italy